Expenses on oncological treatments during the covid-19 pandemic in Ceará, northeast Brazil (Revista Contexto & Saúde, 2026)
Objective: To analyze expenses related to cancer treatment during the Covid-19 pandemic in the state of Ceará. Method: A descriptive study using expense records from the Ceará Hospital Information and High Complexity Procedure Authorization System, developed in 2022. The data were synthesized using Microsoft Excel 2019®. The following measures were used for descriptive analysis: means, standard deviation, minimums, maximums, and an estimate of the mean treatment cost. Results: A reduction in expenses was identified in 2020 (R$ 3,879,505.41) and 2021 (R$ 3,088,822.14) compared to 2019. In 2020, the reduction occurred in May (R$ 2,739,116.44) and June (R$ 2,633,173.82). In 2021, the months included February (R$ 3,193,095.98), April (R$ 3,093,272.64), and May (R$ 3,093,272.64). Surgery reduced the mean values ​​per procedure in 2020 and 2021 (R$ 3,626,046.22; R$ 3,545,102.89), followed by radiotherapy in 2020 (R$ 166,656.00) and chemotherapy (R$ 76,320.89) in 2020, with "adjuvant" treatment being reduced in both years (R$ 95,256.00; R$ 60,710.50). Conclusion: There was a slight reduction in expenses per procedure compared to pre-pandemic levels, but with a relevant assessment considering possible unmet demand during the pandemic.
Keywords: Healthcare expenses; Neoplasms; Coronavirus; Therapeutics